Safety and family satisfaction of a home-delivered chemotherapy program for children with cancer - Lucia De Zen; Irene Del Rizzo; Luca Ronfani; Francesca Barbieri; Marco Rabusin; Roberto Dall'Amico; Egidio Barbi; Margherita Robazza (BMC, 2021)
Abstract Background Home chemotherapy programs for children with cancer are safe and feasible, and their impact on the quality of life has been reported in different countries. A home chemotherapy program was implemented between 2011 and 2019 in an Italian region. This pilot study investigates its safety and feasibility, along with parental satisfaction. Methods Patients between 0 and 18 years diagnosed with malignancy were included. Deceased patients and patients whose families moved abroad or interrupted contact with the service were excluded. Adverse events comprised immediate deterioration of the patient's condition, equipment failure, errors in drug storage, dose or patient identification and personnel safety issues. Parental satisfaction was explored through an email survey of 32 Likert-type and short open questions. Results Thirty-five patients received 419 doses of intravenous chemotherapy at home (cytarabine, vincristine, vinblastine). No adverse events were reported. Twenty-three families out of 25 eligible completed the survey. Most reported being "very satisfied" with the possibility of maintaining a work/domestic routine and reducing time and financial burden of hospital access. Most were "very satisfied" with the opportunity for their child of being less troubled by the treatment. Besides, most reported being "very satisfied" with the chance for healthy siblings of maintaining their routine and coping with their brother/sister's disease. Most perceived the program as safe. All families recommended extending the program to all children in the region. Conclusions This first Italian study supports home chemotherapy as safe and effective, positively influencing the quality of life for children and their families.